Evaluation of a school-based intervention to promote mental health literacy. Preliminary results. (20th October 2021) - Kirchhoff, S; Freţian, A; Wahl, P; Bauer, U
Abstract: Background: Mental illness is one of the leading causes of ill-health and disability. The current COVID-19 pandemic poses an additional challenge on mental health, e.g., through increased levels of anxiety, depression and fears about the future. As most mental illnesses develop before the age of 25, young people are a critical target group for prevention. Mental health literacy (MHL) is considered to be a key determinant of positive mental health, thus, being crucial for mental health promotion and dealing with the aftermath of the pandemic. This project aims at (i) adapting an evidence-based MHL curriculum for German schools, as school-based interventions are suitable in reaching most young people, and (ii) evaluating its acceptance and effectiveness regarding MHL and stigmatizing attitudes. Methods: An interdisciplinary team including representatives from self-help groups for mental health translated and adapted the Canadian "TeenMentalHealth" curriculum for German schools. The evaluation design includes a pre, post, follow-up assessment of MHL, stigmatizing attitudes, and help-seeking efficacy. Results: For better applicability of the curriculum, the original program was shortened, while keeping its core contents such as knowledge and myths around mental health and illness. Written and digital material was developed and distributed to teachers, which were trained to deliver the intervention. Preliminary results show high acceptability, a significant increase in MHL and a decrease in stigmatizing attitudes, while help-seeking efficacy remained unchanged. Conclusions: An MHL intervention was successfully adapted for the German school setting. While evaluation is ongoing, first results indicate its effectiveness in promoting MHL among students, decreasing stigmatizing attitudes and high acceptability, even during the times of the pandemic. Further evaluation is necessary to confirm the preliminary findings and to gain insight into the missing effect on help-seeking efficacy.